Kajian Social Entrepreneur Pengrajin Batik Tulis Di Sentra Batik Al-Barokah Pakandangan Barat Bluto Sumenep Dalam Perspektif Ekonomi Islam - Anshari, Ach Zainal (Jurnal Ekonomika dan Bisnis Islam, 2023)
The diversity and richness of culture in Indonesia, the skills and creativity possessed by human resources are able to produce handicrafts and have very high economic value, such as batik. Batik as one of the creations of the Indonesian people has different patterns, motifs, characteristics and meanings in each region. Like the existence of the Al-Barokah batik center in Pakandangan Barat village, Sumenep is one of the popular batik centers. Starting from a home-based business but having the talent, tenacity, soul to lead and encourage the community to continue making batik, providing training, teaching other communities and managing relationships to advance the economy of the surrounding community. The right effort by starting a business whose value will be donated to sustainable social interests by opening business opportunities without capital for the community to earn income from marketing and the welfare of society, which we can call social entrepreneurs. Having an Islamic economic concept to address social problems and help meet community needs, avoid social inequality with job opportunities, avoid elements of usury and clarity in business.